2009
DOI: 10.1142/s0219887809003825
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanics for the Ricci Flow

Abstract: We construct the classical mechanics associated with a conformally flat Riemannian metric on a compact, n-dimensional manifold without boundary. The corresponding gradient Ricci flow equation turns out to equal the time-dependent Hamilton-Jacobi equation of the mechanics so defined.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…(21) is allowed. 1 Moreover, this dimensionless factor will generally depend on the quantum state under consideration, because both U and I are statedependent. Although the viscosity of the quantum probability fluid depends, through an undetermined dimensionless factor, on the quantum state, the order of magnitude provided by Eq.…”
Section: Computation Of the Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…(21) is allowed. 1 Moreover, this dimensionless factor will generally depend on the quantum state under consideration, because both U and I are statedependent. Although the viscosity of the quantum probability fluid depends, through an undetermined dimensionless factor, on the quantum state, the order of magnitude provided by Eq.…”
Section: Computation Of the Viscositymentioning
confidence: 99%
“…(23) has been dealt with in ref. [1], in connection with the Ricci-flow approach to emergent quantum mechanics; it will also be analysed in a forthcoming publication [12]. For the moment we will relax the requirement that Eq.…”
Section: Exact Solutionsmentioning
confidence: 99%
“…where f (1) and f (2) are to be understood as the values of the function f in the domains 1 and 2 respectively. The basic idea of the method is to investigate the compatibility between some assumed field discontinuities and the structure of a given partial differential equation.…”
Section: Accelerated Photons In Moving Dielectricsmentioning
confidence: 99%
“…Hadamard showed that the differentials of the function f in both domains df (1) = ∂ α f (1) dx α and df (2) = ∂ α f (2) dx α have to be continuous. He then obtained the following crucial result…”
Section: Accelerated Photons In Moving Dielectricsmentioning
confidence: 99%
“…Thus it naturally led many physicists to the attempt to reformulate quantum mechanics in a geometric language, like GR. References [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] are a few such efforts towards the geometrical rewriting of quantum laws.…”
Section: Introductionmentioning
confidence: 99%